Flash Sale Intensity and Delivery Satisfaction: Evidence from Indonesian E-Commerce Platforms - Purwanto, Edy; Marina, Sandriana (Indonesian Scientific Publication, 2024)
This study examines the impact of flash sale intensity on delivery service satisfaction across five critical dimensions: timeliness, product condition, tracking accuracy, return ease, and courier professionalism, focusing on leading Indonesian e-commerce platforms. Flash sales have become one of the most prominent promotional strategies in Indonesia’s rapidly growing digital market, yet they frequently generate logistical challenges such as inventory overload, courier delays, and system inefficiencies. A quantitative survey was conducted with 212 Indonesian consumers who participated in national flash sale events (e.g., 11.11, 12.12). Satisfaction levels were measured using Likert scale items, and the data were analyzed with Pearson correlation and linear regression. The results show significant negative correlations between flash sale intensity and delivery timeliness, product condition, and courier professionalism. Tracking accuracy was moderately affected, while return ease showed no significant relationship. These findings highlight how high-volume promotions strain logistics infrastructure, leading to delivery inefficiencies. The study contributes by filling a research gap in Indonesian e-commerce, offering a multidimensional assessment of delivery service during promotional surges. It recommends practical strategies such as investments in scalable logistics infrastructure, integration of advanced tracking systems, third-party logistics partnerships, and courier training programs to enhance resilience during peak demand. This evidence provides actionable insights for platforms aiming to maintain consumer trust and service quality amid rapid promotional growth.